2016
DOI: 10.1007/jhep10(2016)058
|View full text |Cite
|
Sign up to set email alerts
|

Fermion masses through four-fermion condensates

Abstract: Fermion masses can be generated through four-fermion condensates when symmetries prevent fermion bilinear condensates from forming. This less explored mechanism of fermion mass generation is responsible for making four reduced staggered lattice fermions massive at strong couplings in a lattice model with a local four-fermion coupling. The model has a massless fermion phase at weak couplings and a massive fermion phase at strong couplings. In particular there is no spontaneous symmetry breaking of any lattice s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 67 publications
8
48
0
Order By: Relevance
“…It can be applied to a certain class of fermionic models and it has been found to be very efficient in solving these models. Application of the Fermion Bag approach to our model has been described in detail in [10].…”
Section: Computational Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be applied to a certain class of fermionic models and it has been found to be very efficient in solving these models. Application of the Fermion Bag approach to our model has been described in detail in [10].…”
Section: Computational Approachmentioning
confidence: 99%
“…In this work, we look for a similar continuum limit of the PMS phase using the same model in 4 Euclidean dimensions. A detailed account of this study can be found in [10].…”
Section: Introductionmentioning
confidence: 99%
“…[12]. The conclusion of that work was that a narrow broken phase * smcatter@syr.edu reappears upon lifting the theory from three to four dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…For each flavor the sum gives the Pfaffian of a k × k matrix W ([x; k]), whose matrix elements are given by the free staggered fermion propagator G f (x i , x j ) between the sites in [x; k] [20]. Thus, we obtain…”
Section: The Partition Functionmentioning
confidence: 99%
“…For example it was recently studied extensively in three and four dimensions [17][18][19][20][21] and contains a weak coupling massless fermion phase and a strong coupling massive fermion phase without any spontaneous symmetry breaking. In three dimensions one finds a second order phase transition that separates these two phases.…”
Section: Introductionmentioning
confidence: 99%